2015
DOI: 10.1007/s11302-015-9473-4
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ATP-gated ion channels assembled from P2X2 subunits in mouse cochlear Reissner’s membrane epithelial cells

Abstract: In the cochlea, Reissner's membrane separates the scala media endolymphatic compartment that sustains the positive endocochlear potential and ion composition necessary for sound transduction, from the scala vestibuli perilymphatic compartment. It is known that with sustained elevated sound levels, adenosine 5 -triphosphate (ATP) is released into the endolymph and ATP-gated ion channels on the epithelial cells lining the endolymphatic compartment shunt the electrochemical driving force, contributing to protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Purinergic signaling is sensitive to pathophysiological changes (e.g., due to noise or ischemia) of the extracellular milieu and thereby can promptly react and initiate protective mechanisms. This control function of the purinergic system has been delineated in sound sensitivity of the cochlea and in NIHLs [74,166]. Noise trauma induces various events and purinergic mechanisms are involved in this machinery.…”
Section: Purinergic Signaling and Sensorineural Hearing Lossesmentioning
confidence: 99%
“…Purinergic signaling is sensitive to pathophysiological changes (e.g., due to noise or ischemia) of the extracellular milieu and thereby can promptly react and initiate protective mechanisms. This control function of the purinergic system has been delineated in sound sensitivity of the cochlea and in NIHLs [74,166]. Noise trauma induces various events and purinergic mechanisms are involved in this machinery.…”
Section: Purinergic Signaling and Sensorineural Hearing Lossesmentioning
confidence: 99%
“…The P2X2 receptor is expressed in the cochlea where it is thought to localize to hair cells, as well as Reisner's membrane epithelial cells that maintain the integrity of the endolymphatic compartment (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). ATP released into the endolymphatic compartment in response to loud noise has been proposed to activate P2X2 receptors in the Reisner's membrane and to thereby produce a cation shunt that reduces the endolymphatic potential and the driving force for sound transduction (11).…”
mentioning
confidence: 99%
“…It is known that with sustained elevated sound levels, adenosine 5'‐triphosphate (ATP) is released into the endolymph and ATP‐gated ion channels on the epithelial cells lining the endolymphatic compartment shunt the electrochemical driving force, contributing to protective purinergic hearing adaptation (Housley et al, ; Yan et al, ; Mittal et al, ,c). A study aimed at characterizing the properties of these epithelial cells (Morton‐Jones et al, ). It was concluded that the activation and desensitization properties of the Reissner's membrane epithelial cell ATP‐gated P2 × 2 channel likely contribute to the sensitivity and kinetics of purinergic control of the electrochemical driving force for sound transduction invoked by noise exposure.…”
Section: Complexity Of the Auditory Systemmentioning
confidence: 99%